Screening For Yeast Phytase Leads to the Identification of a New Cell-Bound and Secreted Activity in Cyberlindnera jadinii CJ2 - Capusoni, Claudia; Serra, Immacolata; Donzella, Silvia; Compagno, Concetta (Frontiers in Bioengineering and Biotechnology, 2021)
Phytic acid is an anti-nutritional compound able to chelate proteins and ions. For this reason, food industry is looking for a convenient method which allows its degradation. Phytases are a class of enzymes that catalyse the degradation of phytic acid, and are used as additives in feed-related industrial processes. Due to their industrial importance, our goal was to identify new activities that exhibit best performances in terms of tolerance to high temperature and acid pH. As a result of an initial screening on several yeast species, we focused our attention on phytases found in Cyberlindnera jadinii, Kluyveromyces marxianus and Torulaspora delbrueckeii. In particular, C. jadinii was the one that showed the highest secreted and cell-bound activity, with optimum of temperature and pH at 50 °C and 4.5, respectively. These characteristics suggest that this enzyme could be successfully used for feed as well as for food-related industrial applications.